Functional consequences of neonatal infraorbital nerve section in rat trigeminal ganglion - Jacquin, MF (J Neurosci, 1986)
tandard single-unit recording and stimulation techniques were used to assess the topographic organization, receptive field properties, and projections of cells (n = 297) in the ophthalmic-maxillary part of the trigeminal ganglion in 6 normal adult rats and 15 adults with unilateral infraorbital nerve section at birth (cells recorded ipsilateral to lesion: n = 641; cells recorded on the intact side: n = 223). Stimulating electrodes were placed on the central portion of the regenerate infraorbital nerve and in the trigeminal brain stem subnucleus caudalis in 6 nerve-damaged rats and at equivalent points in 5 normal animals. Data from the normal rats and the intact side of the nerve-damaged animals were identical and were considered together. Of these cells, 73.5% had infraorbital receptive fields. Of these, 77.2% were discharged by vibrissa stimulation (43.8% slow-adapt type I, 10.3% slow-adapt type II, 27.6% low-velocity sensitive rapid adapt, 16.8% high-velocity sensitive rapid adapt, and 1.5% noxious-biased), while the rest responded best to guard hair deflection (12.0%), gentle skin indentation (4.5%), or a strong pinch or deep pressure (6.3%). In stereotaxically matched penetrations in ganglia ipsilateral to the neonatal infraorbital nerve lesions, only 40.6% of the cells had infraorbital receptive fields. Of these, only 37.7% responded to vibrissa stimulation (29.8% slow-adapt type I, 1.2% slow-adapt type II, 2.2% low-velocity sensitive rapid adapt, 32.9% high-velocity sensitive rapid adapt, 33.9% noxious). Other infraorbital cells responded best to guard hair deflection (11.9%), gentle skin indentation (10.8%), or a strong pinch or deep pressure (39.6%). An additional 30 cells did not have a detectable receptive field and were identified only by infraorbital and brain-stem shocks. We also recorded cells with unusual infraorbital receptive fields: 9 units responded to more than 1 vibrissa, 4 were activated by both vibrissa and guard hair deflection, 10 had unusually large skin or deep receptive fields, 1 had a split receptive field, and 7 were discharged only by deep pressure to the region of the nerve section. Seven cells with infraorbital receptive fields were not driven by infraorbital shocks, and 2 were not activated by brain-stem shocks. In normal rats, all cells with infraorbital receptive fields were driven by both electrodes. The percentages of receptive field types for noninfraorbital cells were unchanged in ganglia ipsilateral to the damaged nerve.(ABSTRACT TRUNCATED AT 400 WORDS)